Assessing consumer behavior from a main website of tourism product / Mazturina Mohamed Razak @ Azmi - Razak @ Azmi, Mazturina Mohamed (2013)
Websites have been used as one of the main promotional items in marketing most of tourism products. This encourage governments all over the world to use websites as one of their marketing tools, and to have one to represent a national tourism product would be costly, nonetheless how effective is it compared to other non-official websites remains to be investigated. Therefore by using the Technology Acceptance Model (TAM) model, this study is to examine consumer’s perceived ease of use and perceived usefulness of a website in determining customers’ intention in visiting a tourism attraction. Two original criteria of TAM model was used in this study; future research utilizing an extended TAM to assess the user acceptance. Past researches have proven that the internet is an important influence on consumers’ behavior. The government’s website on homestay is the context of this study and a quantitative approach through distributing structured questionnaires were adopted. Questionnaires were distributed to about 400 participants that are visiting homestays in Selangor. Descriptive statistics and correlation test are used to analyze the data. This research will offer a better understanding on the effectiveness of the website in influencing tourists’ behavior towards a tourism product. Findings clearly revealed that TAM attributes in particular positively influenced consumers’ visit intention. Among these, perceived usefulness variable were to be the prime influencer compared to perceived usefulness of the website.